Spatial distribution of organic carbon contents of Langkawi island coastal waters, Malaysia - Yunus, Kamaruzzaman; Muhamad Tajudin, Nur Shuhada; Saad, Shahbudin; Khan Chowdhury, Ahmed Jalal; Al-Barwani, Said Mohd; Goddard, J Stephen (Oriental Scientific Publishing Co., 2010)
The distribution of total organic carbon content (TOC) in surface sediments of 5 zones in the area of Langkawi Island coastal waters were analysed by using wet oxidation dichromate method. A total of 51 samples were obtained using Ekman Grab from Kuah coastal area (Zone A), Cenang coastal area (Zone B), Datai River (Zone E), Kilim River (Zone D) and Pulau Tuba waters (Zone E). In this study, the highest mean of organic carbon was found in zone A (2.27±0.59), followed by zone C (2.09±0.14), zone D (2.01±0.15), zone E (1.89±0.28) and the lowest is in zone B (1.72±0.38). A relatively weak positive relationship was also found between the organic carbon content and the sediments grain size.